Celebrity Endorsements in Organ Donation Advertisements : Altruism As a Moderator - Sharifah Nurafizah Syed Annuar; Stephen Laison Sondoh Jr; Andreas Totu; Rayner Alfred; Geoffrey Harvey Tanakinjal (2018)
Health and psychology literature suggests the use of celebrity endorsement in organ donation advertisement in changing the attitude to register as organ donors. However, very limited literature was found that discussed the effect of source attractiveness, expertise and trustworthiness towards attitude in the context of organ donation. In addition, there is limited knowledge established in understanding the impact of charisma and authenticity in celebrity studies. The role of altruism as a moderator in the relationship between the attributes of celebrity endorsers and attitude towards organ donation registration is also unclear. Therefore, the purpose of this study is to fill the gaps by determining the impact of celebrity endorser attributes towards attitude towards organ donation. This paper also examines the role of altruism as a moderator to the relationship between celebrity endorser attributes and attitude towards organ donation. The target sample of this study was university students and data collection has been conducted in various universities from four regions in Malaysia. Data from 466 university students were analysed using IBM SPSS Statistics 23 and SmartPLS 3.0. Of five important celebrity endorser attributes that were tested in this paper, the findings show that authenticity and charisma are great predictors to attitude towards organ donation. In addition, the relationship between charisma and attitude is found to be weakened among individuals with high altruism. The findings of this paper are beneficial as they contribute to the celebrity endorsement literature and provide insights to the relevant agencies in selecting celebrity endorsers for their social marketing campaign.